New vistas in rural economy - "Yadav , Subah Singh (ed.) ; Gurjar , Ram Kumar (ed.)" (Jaipur, 1992)
The present set of 5 volumes presents a unique collection of writings on rural economy contributed by outstanding scholars of national and international eminence. It provides comprehensive scenario of the issues and and factors that are vital in the process of accelerating rural economy.
Keywords: Economic India rural regions